Analogical Reversal and Its effect on the establishment of islamic legal rulings according to judge ʿAbd al-Wahhab Al-Baghdadi, through his work (al-Ishraf ala Nukat Masail al-Khilaf) An Applied Study in the Principles of Islamic Jurisprudence.: Study in the Principles of Islamic Jurisprudence (Journal of Academic Research, 2026)
The study addressed the probative authority of analogy by reversal and its deployment in the book Al-Ishraf by Al-Qadi Abd al-Wahhab Al-Baghdadi Al-Maliki. It was structured into an introduction, three sections, and a conclusion. The study relied on a non-exhaustive inductive method in collecting the scholarly material from the work under examination, and on an applied method  in addressing certain issues pertaining to analogy by reversal. It concluded that analogy by reversal constitutes a valid authoritative proof, which the Al-Qadi employed as evidence across various juristic chapters. The conclusion then set out the principal findings intended by the study, and the work was supplemented with a list of sources and references .
Keywords: Abd al-Wahhab; Abd alWahhab; The Original; Derivative; The Ratio Legis